‘Crush Programme’ as Part of Combined Control Programme for Culex Mosquito in Both North and South Dhaka City Corporation (Bangladesh Medical Journal, 2021)
Abstract not availableBangladesh Med J. 2020 Sept; 49(3) : 53-56